Southern annular mode: tropical-extratropical interactions and impacts - Fauchereau, N; Pohl, B; Monteiro, Pedro MS; Reason, C (2009)
25th Annual Conference of the South African Society for Atmospheric Sciences, Tulbagh, South Africa, 9–10 September 2009 In this study the authors investigate in particular its links with the Madden Julian Oscillation and ENSO, the dominant modes of tropical atmospheric variability at the intraseasonal and interannual timescales, respectively. It is showed here that, contrarily to suggestions made in other papers, the SAM is not significantly and unambiguously related to the MJO. On the other hand, we confirm that the SAM shares up to 25% of variance with the ENSO during summer. The independent and combined effects of those modes on Southern African summer rainfall is next investigated and we discuss the importance of a better understanding of tropical – extratropical interactions in the context of the role of the Southern Ocean in modulating fluxes of anthropogenic and natural CO2.